Henri Matisse’s Ecrits et propos sur l’art. A phenomenological inquiry on nature, feeling and origin (Lebenswelt. Aesthetics and philosophy of experience., 2016)
Through a phenomenological reading of Henri Matisse’s Ecrits et propos sur l’art the paper analyzes in their mutual connection the themes of nature, feeling and origin in relation to the Artist’s works (in particular the ones of the Fauvist period) and to his own reflection on art. Interpreting nature through feeling is something more than a solipsistic glance on reality linked to private emotions, it is, according to M. Merleau-Ponty’s theory of perception and expression, a way to create symbols of the living unity of consciousness and the external world. In conclusion, the paper shows the theme of the origin as Matisse’s pictorial way to meditate on the possibility of artistic creation in its necessary connection with the experience of the lifeworld. The constitutive ground of the lifeworld can only be represented into the effort of pure colors and arabesque to show a meditation on the temporal dimension of the origin in which a new disclosing sense can be expressed.